SUICIDE, YOUTH, PSYCHOLOGY, BUNUH DIRI REMAJA PERSPEKTIF PSIKOLOGI DAN HUKUM ISLAM - Ashari ari ari; Nengsih Sri Wahyuni; Laode Agustriono (Muadalah : Jurnal Hukum, 2023)
Age analysis revealed that the number of suicides increased from the ages of 10-16 years, peaked at 26-30 years, and decreased from 46-50 years, with a sharp increase from the age group of 61-65 years to 66-70 years. However, calculating a certain age level reveals that while there is a peak on the curve before 46-50, the rate increases dramatically in the age group 66- 70 years. namely research whose object of study uses library data in the form of books as a data source. Secondary Data Analysis: This method involves analyzing existing data, such as data from health institutions or previous research, to gain insight into youth suicide. Psychological factors that contribute to the risk of suicide in adolescents. Several relevant factors studied in the psychology study of adolescent suicide include: Mental Health Disorders including: Bipolar, breakup, anxiety disorder and schizophrenia. suicide is considered to be strictly prohibited and punishable as a serious sin. Islam teaches the importance of protecting and respecting human life, including one's own life.